Micro-Abrasive Air Jet Machining Technology for Fabrication of Helical Grooves on Bovine Bone - Jialin Li; Quanlai Li; Yafeng Deng; Weipeng Zhang; Haonan Yin (Micromachines)
Biological bone screws play an important role in fixing fractures and bone defects. The machining of helical grooves on xenogenic materials is a key part of fabricating biological bone screws. The fabrication of helical grooves on bovine bone using micro-abrasive air jets was investigated in this paper. The helical groove shapes were classified and their formation mechanisms were studied. Analyses of the material removal mechanism and the effect of process parameters on the groove shapes were carried out. The results show that the helical grooves could be effectively machined using micro-abrasive air jets with a spring mask. The shapes of the helical grooves could be classified as U-, V-, and W-shaped. Cracks that propagated along the cement line may have led to the formation of a slot. Meanwhile, cracks that propagated in the interstitial lamella may have led to the formation of ridges. The slots and ridges resulted in the appearance of stripes on the groove bottom. The cracks propagated along the axial direction of the osteon at the same time as it propagated into the osteon, leading to the formation of dimples on the groove sidewall. The experimental method proposed in this study can be regarded as a suitable method to fabricate helical grooves on bones.